THE ROLE OF ISLAMIC SOCIAL FINANCE IN MITIGATING THE POVERTY LEVELS IN THE POST-PANDEMIC PERIOD - Mohammad Enayet Hossain; Nur Farhah Binti Mahadi; Razali Haron (Journal of Islamic Management Studies, 2023)
The global COVID-19 pandemic has infected millions of people at an alarming rate. The COVID-19 pandemic appeared out of nowhere and has since spread worldwide, with five million deaths recorded globally in just a few months. The economic crisis has prompted global shrinkage, which has resulted in an anticipated economic collapse for 2020–2021. This study examines whether Islamic social finance can effectively mitigate the dangers of humanitarian catastrophes. The study provides a multirange method for maximizing the advantage of Islamic social financing tools such as zakat and waqf. The information, documents, and data for this study are gathered using a qualitative method. The study employed ongoing research, literature review, news stories, reports, and trusted online sources. Eventually, this may add to knowledge by examining the role of Islamic social finance in the current Covid-19 crisis. The findings have consequences for governments and policymakers who want to solve the COVID-19 problem with Islamic social finance ideas and solutions, thereby enhancing people’s social well-being and the global economy’s development.